Sensitive determination of enoxacin in pharmaceutical formulations by its quench effect on the fluorescence of glutathione‐capped CdTe quantum dots. (23rd June 2015) - Yang, Qiong; Tan, Xuanping; Yang, Jidong
Abstract: A sensitive and simple method for the determination of enoxacin (ENX) was developed based on the fluorescence quenching effect of ENX for glutathione (GSH)‐capped CdTe quantum dots (QDs). Under optimum conditions, a good linear relationship was obtained from 4.333 × 10 −9 mol⋅L −1 to 1.4 × 10 −5 mol⋅L −1 with a correlation coefficient (R) of 0.9987, and the detection limit (3σ/K) was 1.313 × 10 −9 mol⋅L −1 . The corresponding mechanism has been proposed on the basis of electron transfer supported by ultraviolet–visible (UV) light absorption, fluorescence spectroscopy, and the measurement of fluorescence lifetime. The method has been applied to the determination of ENX in pharmaceutical formulations (enoxacin gluconate injections and commercial tablets) with satisfactory results. The proposed method manifested several advantages such as high sensitivity, short analysis time, low cost and ease of operation. Copyright © 2015 John Wiley & Sons, Ltd.